Primary sensory and motor cortex function in response to acute muscle pain: A systematic review and meta‐analysis. (23rd February 2016) - Burns, E.; Chipchase, L.S.; Schabrun, S.M.
Abstract: Acute muscle pain has both motor and sensory consequences, yet the effect of muscle pain on the primary sensory (S1) and motor (M1) cortices has yet to be systematically evaluated. Here we aimed to determine the strength of the evidence for (1) altered activation of S1/M1 during and after pain, (2) the temporal profile of any change in activation and (3) the relationship between S1/M1 activity and the symptoms of pain. In September 2015, five electronic databases were systematically searched for neuroimaging and electrophysiological studies investigating the effect of acute experimental muscle pain on S1/M1 in healthy volunteers. Demographic data, methodological characteristics and primary outcomes for each study were extracted for critical appraisal. Meta‐analyses were performed where appropriate. Twenty‐five studies satisfied the inclusion criteria. There was consistent evidence from fMRI for increased S1 activation in the contralateral hemisphere during pain, but insufficient evidence to determine the effect at M1. Meta‐analyses of TMS and EEG data revealed moderate to strong evidence of reduced S1 and corticomotor excitability during and following the resolution of muscle pain. A comprehensive understanding of the temporal profile of altered activity in S1/M1, and the relationship to symptoms of pain, is hampered by differences in methodological design, pain modality and pain severity between studies. Overall, the findings of this review indicate reduced S1 and corticomotor activity during and after resolution of acute muscle pain, mechanisms that could plausibly underpin altered sensorimotor function in pain. What does this review add?: We provide the first systematic evaluation of the primary sensory (S1) and motor (M1) cortex response to acute experimental muscle pain in healthy volunteers. We present evidence from a range of methodologies to provide a comprehensive understanding of the effect of pain on S1/M1. Through meta‐analyses we evaluate the strength of evidence concerning the direction and temporal profile of the S1/M1 response to acute muscle pain.